Zachowania i preferencje turystyczne uczniów Szkoły Podstawowej nr 2 w Koronowie = Tourist behaviour and preferences of students of Elementary School no. 2 in Koronowo - Zbigniew Podgórski; Anna Krolik; Alicja Ewa Tychoniec (Kazimierz Wielki University, 2016)
Podgórski Zbigniew, Krolik Anna, Tychoniec Alicja. Zachowania i preferencje turystyczne uczniów Szkoły Podstawowej nr 2 w Koronowie = Tourist behaviour and preferences of students of Elementary School no. 2 in Koronowo. Journal of Education, Health and Sport. 2016;6(12):625-641. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.220868 http://ojs.ukw.edu.pl/index.php/johs/article/view/4107         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 23.12.2016.       ZACHOWANIA I PREFERENCJE TURYSTYCZNE UCZNIÓW SZKOŁY PODSTAWOWEJ NR 2 W KORONOWIE   TOURIST BEHAVIOUR AND PREFERENCES OF STUDENTS OF ELEMENTARY SCHOOL NO. 2 IN KORONOWO     Zbigniew Podgórski, Anna Krolik, Alicja Tychoniec   Uniwersytet Kazimierza Wielkiego, Polska     STRESZCZENIE: W artykule przedstawiono zachowania i preferencje turystyczne uczniów Szkoły Podstawowej nr 2 w Koronowie. Scharakteryzowano w nim rodzaje wyjazdów, w których uczestniczą dzieci, a także wskazano najważniejsze determinanty podejmowania przez nich aktywności turystycznej. Wyniki badań, dotyczące badanej młodzieży, ukazują częstość ich wyjazdów, terminy i czas trwania podróży oraz odwiedzane obszary. Ponadto zaprezentowano sposób organizacji wypoczynku oraz okreslono osoby przy nim towarzyszące, bazę noclegową i środki transportu. Poprzez badanie ankietowe zainteresowań dzieci walorami turystycznymi i destynacji określono preferencje dzieci względem potencjalnych podróży.   ABSTRACT: The following article analyses tourist behaviour and preferences of students of Elementary School no. 2 in Koronowo. It characterizes kinds of trips which children attend and presents the most important determinants of their tourist activity. Results of the study conducted among students show frequency, time allocation and duration of their trips, as well as visited destinations. Moreover, trips' organisation, travel companions, choice of lodging and transport were all presented as well. The purpose of learning through survey about children's interests in tourist attractions and destinations was to determine their preferences with regard to possible future trips. Słowa kluczowe: uczniowie szkoły podstawowej, aktywność turystyczna, determinanty aktywności turystycznej, rodzaje wyjazdów turystycznych, zachowania i preferencje turystyczne.   Key words: students of elementary school, tourist activity, determinants of tourist activity, kinds of trips of children, tourist behaviour and preferences of children.